Implementasi Nilai-Nilai Moral melalui Pembelajaran Kitabul Akhlaq Lil Banin di Pondok Pesantren Mamba'ul Ulum Jurit Lombok Timur - Ida Fauziah; Edy Herianto; Ahmad Fauzan (PALAPA, 2022)
Kitabul Akhlaq Lil Banin learning is a process of implementing moral values to the student studying at Mamba’ul Ulum Jurit Islamic boarding school, east Lombok. This study aims to determine the implementation of moral values through Kitabul Akhlaq Lil Banin learning, including the content and learning strategies used to change the behavior of students and the advantages and disadvantages of Kitabul Akhlaq Lil Banin learning. The approach used is qualitative type of case study. Data collection using documentations, interviews and observations. Based on the result of study, it shows that Kitabul Akhlaq Lil Banin contains moral values related to the values of tolerance, discipline and responsibility. Which in learning use the Bandongan method or wetonan. The implementation of Kitabul Akhlaq Lil Banin learning has an impact on the behavior of students. The implementation of this learning also contains advantages and disadvantages in term of three factors namely teacher,students and infrastructure.